Taxonomic reconsideration of Prunus veitchii (Rosaceae) - Baohuan Wu; Chaoyu Liu; Daniel Potter; Dafang Cui (PhytoKeys, 2019)
Prunus veitchii was published in 1912 and was treated as a synonym of P. serrulata var. pubescens. The information about this taxon is relatively scarce. When consulting specimens of Prunus L., type materials of Prunus veitchii were found to belong to three taxa and P. veitchii, P. concinna, P. japonica var. zhejiangensis, C. jingningensis and C. xueluoensis were found to be conspecific. The taxonomic status of P. veitchii is reconsidered in the present paper. Morphometric analyses were performed to evaluate the significance of differences between P. veitchii and P. serrulata var. pubescens. The results show that the leaves of P. veitchii are significantly smaller and narrower than the leaves of P. serrulata var. pubescens and the peduncle and pedicels are shorter. According to the results of morphometric analyses, P. veitchii should be treated as a separate species. To address these results, a lectotype of P. veitchii is designated here and P. concinna, Cerasus jingningensis and C. xueluoensis are here designated as synonyms of P. veitchii.